“Di excogitato dignissimo”. I monumenti funerari nell’Hypnerotomachia Poliphili .......... 197 - Knechtel, Miriam (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
The funerary architecture, which is described in different parts of the Hypnerotomachia in various contexts and levels of detail, significantly contributes to the ambiguous and mysterious nature of the work of Francesco Colonna. The idea behind this short article is to approach all these constructions in their entirety. Based on an overview regarding structure, form, dimension and details of all commemorative monuments mentioned in the book, the architectural descriptions will be analysed not only with regard to potential influences of the ancient funerary architecture of Italy, but also concerning their composition, their meaning, their multidimensional nature and also the relation between text and woodcuts. The article cites various monuments which might have been appropriate sources of inspiration and suggests that the descriptions serve both the presentation of a profound knowledge in the field of architecture on the part of the author and an intellectual challenge for the reader. Moreover, the study shows that the contradictions in the text regarding the funerary monuments as well as the discrepancies between the descriptions and illustrations might have been incorporated intentionally by the author, in order to test the reader once more and to transfer the sometimes illogical nature of the dream world to the funerary architecture and also to its visualisation.